REVEALING THE HIDDEN MASK: A CASE ON PRIMARY HYPERPARATHYROIDISM MIMICKING PREGNANCY SYMPTOMS - Hamizah, Hamzah; Chua, Yi Jiang; Samsuddin, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Parathyroid adenoma in pregnancy is uncommon, posing diagnostic and treatment challenges. We report a case of primary hyperparathyroidism (PHPT) due to a parathyroid adenoma successfully treated with surgery during pregnancy. CASE A 20-year-old female, gravida 2 para 0+1, presented with vomiting since the fourth week of pregnancy. She also reported experiencing left shoulder pain, abdominal discomfort, polyuria, nocturia, and constipation. Initially diagnosed with hyperemesis gravidarum, further investigation revealed hypercalcemia with a serum calcium level of 3.66 mmol/L, phosphate level of 0.7 mmol/L, and markedly elevated intact parathyroid hormone (iPTH) at 15.53 pmol/L (normal value: 1.6-6.9 pmol/L). Despite attempts to lower calcium levels through hydration and diuresis with furosemide, her serum calcium remained elevated at 3.14 mmol/L. She received six doses of subcutaneous calcitonin due to persistent hypercalcemia, resulting in a reduction of calcium to 2.83 mmol/L. Ultrasonography of the neck detected a left superior parathyroid adenoma. At 25 weeks of gestation, she underwent a successful left superior parathyroidectomy with intraoperative parathyroid hormone monitoring, resulting in positive outcomes for both mother and baby. We described a case of PHPT secondary to a parathyroid adenoma presenting with typical pregnancy symptoms. A high index of suspicion warrants screening for serum calcium levels in hyperemesis gravidarum if symptoms persist beyond the first trimester or are severe, and if symptoms suggestive of hypercalcemia are present. Early detection is crucial for the timely management and improvement of maternal and foetal outcomes. Maternal complications can be as high as 67% including nephrolithiasis, pancreatitis, hyperemesis gravidarum, muscle weakness, confusion, hypercalcaemic crisis, and can also lead to miscarriages and pre-eclampsia. CONCLUSION Recognizing primary hyperparathyroidism can be challenging as symptoms may overlap with typical pregnancy. Surgery is the sole curative measure for primary hyperparathyroidism, well-tolerated during pregnancy with minimal adverse effects.